Indications and Limitations of Bariatric Intervention in Severely Obese Children and Adolescents With and Without Nonalcoholic Steatohepatitis. Issue 4 (April 2015) - Nobili, Valerio; Vajro, Pietro; Dezsofi, Antal; Fischler, Bjorn; Hadzic, Nedim; Jahnel, Joerg; Lamireau, Thierry; McKiernan, Patrick; McLin, Valerie; Socha, Piotr; Tizzard, Sarah; Baumann, Ulrich
<x xml:space="preserve">Abstract</x> ABSTRACT Morbid obesity is strongly associated with nonalcoholic fatty liver disease (NAFLD), which is one of the most common causes of chronic liver disease worldwide. The present best treatment for NAFLD and nonalcoholic steatohepatitis (NASH) is weight reduction through lifestyle modification. Because of frustrating inefficiency of such a therapeutic approach, bariatric surgery is increasingly performed in adolescents as an alternative option for weight reduction. Standards of care and consensus for indications are, however, scarce. We explore the indications and limitations of bariatric surgery in children with severe obesity with and without NASH and aim to provide guidance for the exceptional indications for adolescents with extreme obesity with major comorbidity that may benefit from these controversial interventions. Present evidence suggests that bariatric surgery can decrease the grade of steatosis, hepatic inflammation, and fibrosis in NASH. Uncomplicated NAFLD is not an indication for bariatric surgery. Roux-en-Y gastric bypass is considered a safe and effective option for adolescents with extreme obesity, as long as an appropriate long-term follow-up is provided. Laparoscopic adjustable gastric banding has not been approved by the Food and Drug Administration for use in adolescents and therefore should be considered investigational. Finally, sleeve gastrectomy and other types of weight loss surgery that have grown increasingly common in adults, still need to be considered investigational. Temporary devices may be increasingly being used in pediatrics; however, future studies, including a long-term risk analysis of patients who undergo surgery, are much needed to clarify the exact indications for bariatric surgery in adolescents.